IMPLEMENTASI METODE DOUBLE EXPONENTIAL SMOOTHING HOLT PADA PERAMALAN IPM DI KALIMANTAN TIMUR - Muhammad Irfan Zaky; Amin Padmo Azam Masa; Islamiyah, Islamiyah (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2024)
Human Development Index (HDI) is a human development measuring tool introduced by the UNDP in 1990. Based on data from the East Kalimantan Central Statistics Agency (BPS), since 2010, the East Kalimantan Province HDI has experienced an upward trend with a decline in 2020 due to pandemic . In 2022, East Kalimantan Central Statistics Agency recorded the HDI value for East Kalimantan as reaching 77.44. This achievement makes East Kalimantan Province a province with a high level of human development and the 3rd ranked province with the highest HDI nationally. Based on this ranking, there is still room for the government to increase the HDI value of East Kalimantan to prepare it to become the new capital of the country. Therefore, a forecast is needed to find out the HDI value of East Kalimantan Province for the next few years as a consideration for the government in making policies. One forecasting method that can be used to predict the HDI of East Kalimantan Province is Holt's Double Exponential Smoothing (DES). The results obtained from DES Holt forecasting of HDI data for East Kalimantan Province for 2023-2027 are 77.95; 78.46; 78.98; 79.49; 80.01 with a Mean Absolute Percentage Error value of 0.229%.